Adapting an evidence-based HIV prevention intervention for pregnant African-American women in substance abuse treatment - Winona Poulton; Felicia A Browne; Wendee M Wechsberg; et al (Dove Medical Press, 2011)
Wendee M Wechsberg1, Felicia A Browne1, Winona Poulton1, Rachel Middlesteadt Ellerson1, Ashley Simons-Rudolph1, Deborah Haller2,  1RTI International,* Research Triangle Park, NC, USA; 2Columbia University College of Physicians and Surgeons, New York, NY, USA,  *RTI International is a trade name of Research Triangle InstituteAbstract: An adaptation of an evidence-based, woman-focused intervention designed to reduce HIV risk behaviors was conducted for pregnant, African-American women in substance abuse treatment in North Carolina. The intervention adaptation process included focus groups, expert panels, and the filming of women who spoke about their experiences with pregnancy, drug use, sex risk behaviors, HIV testing and treatment, need for substance abuse treatment, violence, and victimization. The assessment instrument was adapted for pregnant women and the intervention was organized into a 4-session PowerPoint presentation, with an additional session if a woman tested positive for HIV. All sessions and assessment instrument were installed on laptop computers for portability in treatment programs. We pilot tested our adaptation with 59 pregnant African-American women who had used an illicit drug within the past year and were enrolled in substance abuse treatment. At baseline, 41% were currently homeless, 76% were unemployed, 90% had not planned their current pregnancy, and approximately 70% reported drug use since finding out about the pregnancy. This sample of participants rated the intervention sessions and were highly satisfied with their experience, resulting in a mean satisfaction score of 6.5 out of 7. Pregnant African-American women who use drugs need substance abuse treatment that they do not currently access. Woman-focused HIV interventions help to address intersecting risk behaviors and need for treatment prevalent among this vulnerable group.Keywords: African-American woman, HIV prevention pregnancy, drug use, violence, sexual risk